Pengaruh Lingkungan Belajar, Fasilitas, dan Metode Mengajar Guru melalui Motivasi terhadap Hasil Belajar - Wardani Wardani (Mahesa Research Center, 2021)
The research purpose is to knowing the effect of enviromental education in school, education facilities, the teacher learning method through learning motivation to the learning social studies result. The research method used descriptif verifikator, ex post facto and survey. The collection data technique using questionnaire and test. The taking sample technique is approached simple random sampling. The amount of sample is 144 students on SMPN 22 Bandar Lampung. The data analysis using track analysis and Structural Equation Modeling (SEM). The research result showing that there's a positive relation lickages between endogenous variable, exogenous variable, and intervening variable. Can be concluded that if learning enviroment in school, learning facilities, the teacher learning good method will have an impact on good motivation and also good learning result.